A Rare Case of Deep Digital Flexor Tendinopathy following Centesis of the Navicular Bursa - Froydenlund, Tim J.; Meehan, Lucinda J.; Morrison, Linda R.; Labens, Raphael (Frontiers in Veterinary Science, 2017)
Navicular bursa centesis is a common diagnostic and therapeutic procedure in equine practice. This case report documents the clinical, diagnostic imaging and histological findings in a horse with a suspected iatrogenic deep digital flexor tendon (DDFT) injury following centesis of the navicular bursa via a modified distal plantar approach (placement of two needles in a weight bearing position). Although it cannot be proven with absolute certainty, the authors believe that this is the first reported case where navicular bursa centesis is the likely cause of a DDFT lesion, and with magnetic resonance imaging performed both pre- and post-centesis. With this potential, though rare, complication of the procedure, alternative tendon sparing injection techniques should be considered prior to navicular bursa centesis in certain cases.